Study on Pattern of Electrolyte Changes in Dengue Syndrome Patients in a Tertiary Level Hospital - Majumder, Moitreyee; Biswas, Sajalendu; Khanduker, Sadia (Journal of Shaheed Suhrawardy Medical College, 2023)
Background: Dengue is an acute systemic viral disease that has established itself globally in both endemic and epidemic transmission cycles. The disease is spread by the bite of an Aedes mosquito. Electrolyte disturbances is a major complication in dengue infection. In present study serum sodium, potassium & chloride level was estimated to find the electrolyte abnormality in dengue patients. Material & Methods: This prospective cross sectional study was done on 121 adult patients of “Shaheed Suhrawardy Medical College, Hospital” from August 2019 to April 2020 who were tested positive by NS1 or IgM for dengue. Result: Mean age of dengue patients was 31.17 ± 11.8 yrs. Higher percentage (57.85%) of dengue patients were observed in young age group (i.e. 18-30 yrs.) than any other age group. Mean value of serum electrolytes was 139.34±3.76 meq/L, 4.48±.74 meq/L & 101.1±3.55 meq/L for sodium, potassium & chloride respectively. Mean value of all electrolytes are higher in dengue fever than dengue hemorrhagic fever though there was no significant statistical difference. Among all the dengue patients 10.7% had hyponatremia, 4.1% had hypernatremia and 85.1% had normal serum sodium. Regarding serum potassium status 9.92% had hypokalemia, 17.36% % had hyperkalemia and 72.72% had normal serum potassium. Conclusions: Young male population aged 18-30 yrs is more prone to dengue infection. Common electrolyte disturbances in dengue infection are hyponatremia and hyperkalemia. J Shaheed Suhrawardy Med Coll 2021; 13(2): 105-108